2011
DOI: 10.1017/s0022109011000135
|View full text |Cite
|
Sign up to set email alerts
|

New Methods for Inference in Long-Horizon Regressions

Abstract: I develop new results for long-horizon predictive regressions with overlapping observations. I show that rather than using autocorrelation robust standard errors, the standard t-statistic can simply be divided by the square root of the forecasting horizon to correct for the effects of the overlap in the data. Further, when the regressors are persistent and endogenous, the long-run ordinary least squares (OLS) estimator suffers from the same problems as the short-run OLS estimator, and it is shown how similar c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
57
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 78 publications
(59 citation statements)
references
References 40 publications
2
57
0
Order By: Relevance
“…In order to evaluate the power properties of long-horizon tests, I rely on recent test statistics developed by Valkanov (2003) and Hjalmarsson (2011), which have been shown to control size well. Use of overlapping observations induces strong serial correlation in the regression residuals and standard errors that fail to account for this fact lead to biased inference.…”
Section: Test Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to evaluate the power properties of long-horizon tests, I rely on recent test statistics developed by Valkanov (2003) and Hjalmarsson (2011), which have been shown to control size well. Use of overlapping observations induces strong serial correlation in the regression residuals and standard errors that fail to account for this fact lead to biased inference.…”
Section: Test Proceduresmentioning
confidence: 99%
“…This is true both for Valkanov's (2003) test, but also if one uses, for instance, Newey-West standard errors in a normal t-statistic. The test proposed by Hjalmarsson (2011) specifically for the case of endogenous regressors does not suffer from this problem. These findings add an extra note of caution to the use of long-horizon regressions.…”
Section: Introductionmentioning
confidence: 99%
“…In this paper, we propose a local-asymptotic model that builds on the work of Kemp (1999), Valkanov (2003), Torous et al (2004), Chevillon and Hendry (2005) and Hjalmarsson (2011). We prove a new key property of direct multi-step estimators, namely their robustness to misspecification of the serial correlation of the error process.…”
Section: Introduction and Overviewmentioning
confidence: 88%
“…The empirical literature has shown that whereas H h=1 0 often does not reject, this is not the case when considering large h, in which case H h 0 may reject and y t−h appears helpful in predicting z t . The question of how large h should be is an empirical one: Hjalmarsson (2011) studies the case where h is fixed, whereas Valkanov (2003), Torous et al (2004) and Hjalmarsson (2011) have considered letting the horizon grow with the sample size T as respectively h = O (T ) and h = o (T ) . In their setting, Torous et al and Hjalmarsson allowed in addition for the error (ε t+1 , t+1 ) to exhibit autocorrelation.…”
Section: The Models and Local-asymptotic Assumptionsmentioning
confidence: 99%
See 1 more Smart Citation